Psychometric evaluation of Stanford health assessment questionnaire 8-item disability index (HAQ 8-item DI) in elderly people - Zahra Tagharrobi; Khadije Sharifi; Zahra Sooky (Journal of Holistic Nursing and Midwifery)
Introduction: Measuring level of disability in elderly in attention to their physical status requires an instrument practicable in elderly and easy to score.